Towards Education 6.0: Reconstructing the Future Paradigm of Islamic Religious Education through Artificial Intelligence, Sustainability, and Spiritual Intelligence - Najeeb Yahya; Mowafg Masuwd; Helene Knudstad; Md. Sultan Mahmud (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
Educational transformation continues to evolve beyond Education 4.0 and Society 5.0 toward the emerging concept of Education 6.0, emphasizing intelligent technologies, sustainability, global citizenship, and holistic human development. Islamic Religious Education must proactively respond to this paradigm shift while preserving its foundational spiritual and ethical principles. This study aims to reconstruct the future paradigm of Islamic Religious Education by integrating artificial intelligence, sustainability education, spiritual intelligence, and transformative pedagogy. A qualitative conceptual research design employing systematic literature review and theoretical synthesis was conducted. The findings suggest that future Islamic education should prioritize adaptive learning, AI-assisted instruction, interdisciplinary curriculum design, ecological responsibility, ethical digital citizenship, and lifelong spiritual development. The proposed framework positions Islamic education as a catalyst for producing globally competent, technologically literate, morally responsible, and spiritually grounded learners capable of addressing future societal challenges. The novelty of this study is the formulation of the Education 6.0 Islamic Learning Ecosystem, a comprehensive theoretical model integrating emerging technologies, sustainable education, human-centered innovation, and Islamic educational philosophy as the foundation for the future of Islamic Religious Education